Financing High-Tech Startups Using Productive Signaling to Efficiently Overcome the Liability of Complexity - Tech, Robin P. G. (Springer International Publishing, 2018)
This book examines the adverse effects of complexity, information asymmetries, transaction costs, and uncertainty on investors' decision making. It suggests mitigating those effects using appropriate and matching signals, and analyzes a sample of 903 German startups to quantitatively highlight the distinct financing patterns and characteristics of high-tech startups. It then investigates the reasons for these patterns on the basis of a qualitative study that includes 34 interviews with investors and entrepreneurs in the US and Germany and an international expert panel. Lastly, it presents a framework that matches complexity factors with appropriate productive signals. .